Case Studies on Marriage for Children Who Have Not Reached the Age Limit - Zefanya Angellin Chen; Vanessa Vanessa; Felicia Amanda Sulistio (CV. Rayyan Dwi Bharata, 2023)
Marriage is a living union for the legalization of sexual relations and to obtain offspring or children, which is regulated by the rule of law. Article 1 of the Law of the Republic of Indonesia Number 1 of 1974 concerning Marriage states that